2020
DOI: 10.3390/ijms21082887
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxybutyrate Is Active Compound in Flax that Upregulates Genes Involved in DNA Methylation

Abstract: In mammalian cells, 3-hydroxybutyrate (3-HB) is not only an intermediate metabolite during the oxidation of fatty acids, but also an important signaling molecule. On the other hand, the information about the metabolism or function of this compound in plants is scarce. In our study, we show for the first time that this compound naturally occurs in flax. The expression of bacterial β-ketothiolase in flax affects expression of endogenous genes of the 3-HB biosynthesis pathway and the compound content. The increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…However, there are reports that PHB can also be synthesized naturally in plants [ 15 , 154 ]. The work of Mierziak et al proves that 3-hydroxybutyrate occurs naturally in flax [ 155 ]. It is not yet possible to identify the origin of 3-HB in plants.…”
Section: The Role Of Beta-hydroxybutyrate In Plantsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there are reports that PHB can also be synthesized naturally in plants [ 15 , 154 ]. The work of Mierziak et al proves that 3-hydroxybutyrate occurs naturally in flax [ 155 ]. It is not yet possible to identify the origin of 3-HB in plants.…”
Section: The Role Of Beta-hydroxybutyrate In Plantsmentioning
confidence: 99%
“…Another possibility is de novo synthesis from acetyl-CoA or another as yet undiscovered metabolic pathway. As mentioned earlier, plants contain enzymes that are involved in the synthesis of 3-HB in bacteria [ 15 , 130 , 155 ]. Flax with the introduced bacterial β-ketothiolase gene (the first enzyme in the 3-HB synthesis pathway) showed an increased content of 3-HB as well as overexpression of the endogenous plant beta-ketothiolase gene.…”
Section: The Role Of Beta-hydroxybutyrate In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Differently from animals, in which 3-OH-butyrate is an intermediate metabolite of fatty acids, the physiological importance and the metabolism of 3-OH-butyrate in plants are not fully understood and characterized. Mierziak et al ( 2020 ) demonstrated that 3-OH-butyrate occurs naturally in flax and could act as a regulatory molecule that most likely influences the expression of genes involved in DNA methylation, thereby altering DNA methylation levels. Recent studies showed that plants contain enzymes such as β-ketothiolase (EC 2.3.1.9) and acetoacetyl-CoA-reductase (EC 1.1.1.36), which are involved in the synthesis of 3-OH-butyrate as in bacteria and animals (Xu et al, 1997 ; Beaudoin et al, 2009 ; Jin et al, 2012 ; Tsuda et al, 2016 ; Mierziak et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%